EDUTRACE: A Web Based Early Warning System for Detecting Out-of-School Children in Tasikmalaya - Dasya Arief Firmansyah; Jovita Edgina; Irfan Nafis Sjamsuddin (Deparment Information System, Siliwangi University, 2026)
The problem of out-of-school children (OTS) is one of the most persistent challenges in the Indonesian education system. Tasikmalaya Regency recorded 29,949 children aged 7–18 years who were not receiving education as of October 2025, while West Java reported 658,831 OTS, the highest absolute figure nationally. The persistence of this problem is caused by three systemic gaps: fragmentation between the Dapodik (Ministry of Education and Culture) and EMIS (Ministry of Religious Affairs) data systems, the absence of an early warning mechanism to identify at-risk students before they drop out, and the unregistered status of thousands of salafiyah Islamic boarding schools (pesantren) whose students are incorrectly classified as OTS. This paper presents the design and development of a prototype of EDUTRACE (Education Tracking and Early Alert System), a web-based information system developed using React, TypeScript, Vite, and Tailwind CSS. The system integrates data from various educational registries, provides a machine learning-based risk assessment mechanism for early identification of at-risk students, and automates notification to stakeholders. The research used a literature review methodology combined with prototype development, without formal usability testing. The resulting prototype demonstrates the feasibility of a data-driven, preventive approach to addressing ATS in a local government context. EDUTRACE contributes to the achievement of SDG 4 (Quality Education), specifically Targets 4.1, 4.5, and 4.6, by enabling earlier and more targeted educational interventions. The system's modular architecture allows for phased implementation across schools, villages, and sub-district education offices.